200 anos de “Independência” interditando a formação “nacional-popular” do Brasil - Semeraro, Giovanni; Lole, Ana (International Gramsci Journal, 2023)
200 years after 7 September 1822, when Don Pedro I, Crown Prince of Portugal, pro-claimed the Independence of Brazil, this article presents a critical analysis of the event, highlighting the contradictions of this historical period and the challenges that arise for the formation of Brazil as a nation. Situated within the process of modernity established by capitalist globalization, the ‘independence’ of Brazil occurred as a subordinate insertion in world geopolitics. Contrary to the official discourse of a sovereign country and the mystified narratives of ‘the cordial man’ and ‘racial democracy’ spread among the population, these pages question the process of formation of a country founded on genocide, slavery, the exclusion of great part of the population of basic rights, dis-crimination and violence systematically practised to block the constitution of a demo-cratic project of a national-popular character. This notwithstanding, the second part of the article shows how, over these 200 years, a myriad of admirable social and popular struggles have been fertilizing the ground for Brazil to completely free itself from the colonial condition and become an effectively independent and sovereign nation.